The Effect of Digital Marketing and Customer Satisfaction on Company Image And Its Impact on Customer Loyalty Local Water Supply Utility (PDAM) Semarang Regency - Yahya Yahya; Harry Soesanto (PT. Publikasiku Academic Solution, 2023)
Water, as a vital element needed by all living entities, including humans, is an irreplaceable staple in today's global ecosystem. Its presence has a crucial role in maintaining human survival. As a result, the responsibility for overall water management falls on the government as the main regulator in this regard. The basis for this research is due to the research gap and to strengthen theories about digital marketing on customer satisfaction and digital marketing and customer satisfaction on company image. The research method used is